Peran Otoritas Jasa Keuangan dalam Pengawasan dan Pengaturan Lembaga Keuangan di Indonesia - Nurdin, Aulia Anjani; Darussalam, Rezky Fabyo; Asri, Muh Rozi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Financial Services Authority (OJK) has an important role in supervising and regulating financial institutions in Indonesia. As an independent institution established based on Law Number 21 of 2011, OJK is tasked with maintaining financial system stability, protecting consumers, and encouraging transparency in the financial sector. OJK's main functions include supervision of banking, capital markets and the non-bank financial industry (IKNB) such as insurance and pension funds. Supervision carried out by OJK includes aspects of licensing, regulations and law enforcement, as well as monitoring good governance practices. In carrying out its functions, OJK faces challenges such as the complexity of financial products and systemic risks which can have a broad impact on the economy. The OJK's role is increasingly significant amidst the rapid development of financial technology, so innovation in regulations is needed to maintain a balance between industrial development and consumer protection. This abstract discusses the role faced by the OJK in supervising and regulating financial institutions in Indonesia.